Physical models of the bidirectional reflectance of solar receiver coatings. (October 2020) - Bitterling, Moritz; Bern, Gregor; Wilson, Helen Rose; Heimsath, Anna; Nitz, Peter
Highlights: Investigation of optical properties of a widely used coating for solar absorbers. Measurement of reflectance properties, dependent on incidence and emergence angles. Description of the data with models featuring only physically meaningful parameters. Abstract: We present measurements of the Bidirectional Reflectance Distribution Function (BRDF) of the state-of-the art solar receiver coating, Pyromark® 2500, and show how the data can be accurately described with physical models. In the conducted measurements of the receiver coating, a peak shift of the radiation away from the direction of ideal specular reflection was observed. Both the Cook–Torrance and the He–Torrance models reproduce this behaviour. For the application of the former model, an empirical angular dependence of the parameter describing the surface roughness has to be assumed in order to obtain an adequate fit to the data. The latter model is less exact in a statistical sense, but it is physically based, with six meaningful fit parameters. As we found that the He–Torrance model with its original form of the specular reflection yielded physically incorrect results for incidence angles larger than 80°, a modification is proposed to overcome this deficiency. Overall, the fitted models are able to provide a good description of the BRDF of the receiver coating over three orders of magnitude. Our results can play an important role in facilitating camera-based flux control or optical simulations of solar tower systems. Moreover, we think that our findings can serve as a sound starting point for the physical modelling of other absorber coatings currently being developed.